Private Equity and Industry Performance - Bernstein, Shai; Lerner, Josh; Sorensen, Morten; Strömberg, Per (Management Science, 2017)
The growth of the private equity industry has spurred concerns about its impact on the economy. This analysis looks across nations and industries to assess the impact of private equity on industry performance. We find that industries where private equity funds invest grow more quickly in terms of total production and employment and appear less exposed to aggregate shocks. Our robustness tests provide some evidence that is consistent with our effects being driven by our preferred channel. This paper was accepted by Amit Seru, finance.